Subjective evaluation of the knowledge of the secondary school youth pertaining - Kanadys, Katarzyna; Lewicka, Magdalena; Niziołek, Iwona; Bąk, Magdalena; Stawarz, Barbara; Wiktor, Henryk (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The knowledge of young people pertaining the physiology of the menstrual cycle is an important indicator of the pro-health education of the society. There are not many reports as for this problem if one takes into account the indexed positions in Medline basis. Aim of the study. The aim of the study was the evaluation of the subjective knowledge as for the physiology of the menstrual cycle of a woman. Materials and methods. The study was conducted on randomly chosen 160 individuals of secondary schools by the use of a questionnaire of authors’ invention. The obtained results were subjected to statistical analysis admitting a 5% risk of an inference error. Results and conclusions. Basing on the studies conducted, it was fund that the state of the young people’s knowledge pertaining to the knowledge of the menstrual cycle of a woman is usually satisfactory. The majority of the studied youth of secondary schools as the first day of the menstrual cycle gave the first day of menstruation. Our own studies showed that the studied youth had an insufficient knowledge pertaining to the stages of the menstrual cycle of a woman. By the opinion of the examined youth, the body’s temperature after ovulation rises. Nursing Topics 2010; 18 (3): 292-298